Between Theoretical Sharia and Practical Realities: A Critical Analysis of Interfaith Marriage in Classical Texts and Contemporary Legal Contexts - Nasrulloh, Muhammad; Witro, Doli; Baskoro, Aji; Ahmad, Sabarudin; Ermawan, Muhammad Zakky Ubaid; Alghani, Raid (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2025)
Islamic law does not categorically prohibit all forms of interfaith marriage. However, this permissibility requires critical re-examination in light of contemporary socio-legal realities. In the Indonesian context, the increasing occurrence of interfaith marriages, compounded by the issuance of Supreme Court Circular (SEMA) No. 2 of 2023, which explicitly prohibits their recognition, raises urgent questions regarding the relevance and applicability of classical Islamic legal doctrines in modern legal systems. This article explores whether the permissibility of interfaith marriage in Islamic law is both theoretically coherent and practically feasible, or whether it remains a doctrinal ideal with limited applicability in real-world contexts. Utilizing a normative legal methodology that incorporates conceptual, statutory, and historical approaches, and employing a contemporary fiqh-based analysis, the study argues that the marriage of a Muslim man to a Christian or Jewish woman (ahl al-kitāb) remains valid under classical Islamic jurisprudence (fiqh). Nevertheless, such permissibility should not be generalized as a communal norm, especially within Muslim-majority societies. Instead, interfaith marriages should be addressed on a case-by-case basis, particularly in exceptional circumstances, such as in non-Muslim majority societies where access to Muslim partners is severely limited, including certain localities in Indonesia. The findings highlight the significance of contextual legal reasoning (ijtihād) and the discretionary application of Islamic legal norms in accommodating interfaith marriages within Indonesia's pluralistic legal and social framework.